Reforma Psiquiátrica (im)possível? Estudo documental e analítico (2008 A 2017) - Fernades, Cristofthe Jonath (2018)
The research problem of this work is whether the Brazilian psychiatric reform has reached their goals. We start from the conception of deinstitutionalization as the objective of psychiatric reform, meaning the creation of fully substitutive services to the Psychiatric Hospital and the alteration of the legal status of the person in mental distress. To answer the question posed, we conducted a bibliographic review, consisting of three corpora. The first corpus was composed of indexed bibliographic production in the Portal Of Capes, in the period 2001 to 2017, which was analyzed if there was pertinence of the conception of deinstitutionalization, as objective of the most current brazilian psychiatric reform. The second corpus constituted of the last three legislative documents, what focused on mental health care in Brazil. The third corpus was built with the data of offers of psychiatric and substitutive services in Brazil, in the period 2008 to 2017. In the analysis of the bibliographic production, 12 categories were created that grouped the 166 forms of use of the term deinstitutionalization identified, which present a non-consensual scenario, indicating a field of political dispute in the appointment of this experience. The legislative analysis evidenced advances in the rights of the subject assisted by mental health care, because not listed in latest legislation the immediate loss of the civilian capacity of the subject hospitalized in a psychiatric hospital, however was verified the perpetuation of the modalities of involuntary and compulsory psychiatric internment, already in force in the legislation of the year 1934. The analysis of the quantitative data on the provision of mental health care services allowed us to verify the occurrence of reducing the number of beds, the number of internment and of billing of psychiatric hospitals. It was also observed that there was an advance in the supply of the various services of community emphasis, however the number of municipalities attended by these services remained restricted and concentrated in specific regions of the country. Thus, a scenario was identified questionable of the consolidation of the psychiatric reform, due to the ways in which the process of achieving its objectives.